Extraction from Thermopsis turcica plant and its analysis (Texas Journal of Multidisciplinary Studies, 2024)
Thermopsis turcica is an endemic species present in Türkiye and it is seen as a source of functional compounds such as antioxidant phenolics. Even though some biological activities of the aerial parts of T. turcica have been determined, knowledge regarding the organ-specific chemical composition and effects on human breast cancer is still scarce. Therefore, the present study aims to evaluate the antioxidant capacities, phenolic acid profiles, and potential biological activities of methanol extracts obtained from the leaf, flower, and stem tissues of T. turcica